1989
DOI: 10.1037/0096-1523.15.3.529
|View full text |Cite
|
Sign up to set email alerts
|

Speed and accuracy of saccadic eye movements: Characteristics of impulse variability in the oculomotor system.

Abstract: Dynamic characteristics observed in the trajectories of saccadic eye movements reveal systematic variability of the force pulses used to move the eyes. This variability causes saccades to exhibit a linear speed-accuracy trade-off: As the average distance and duration of saccades toward specified target points increase, the standard deviations of saccadic-movement endpoints increase linearly with the saccades' average velocity. The linear trade-off, and other observed stochastic properties of saccades, may be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
147
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(164 citation statements)
references
References 57 publications
16
147
0
1
Order By: Relevance
“…An occasionalexperiment (we found two, both conducted by the same primary investigator: Abrams & Jonides, 1988;Abrams, Meyer, & Kornblum, 1989) has been designed so that the eye tracker calibration was objectivelyverified before every trial and the actual test criterion was reported in the experimental write-up. In each experiment, the participant was instructed to fixate a set of crosshairs between each trial, and the output of the eye tracker is automatically verified to be within range of this location on the display.…”
Section: Problem 2: When Eye Tracker Accuracy Deteriorates Below a Thmentioning
confidence: 99%
See 1 more Smart Citation
“…An occasionalexperiment (we found two, both conducted by the same primary investigator: Abrams & Jonides, 1988;Abrams, Meyer, & Kornblum, 1989) has been designed so that the eye tracker calibration was objectivelyverified before every trial and the actual test criterion was reported in the experimental write-up. In each experiment, the participant was instructed to fixate a set of crosshairs between each trial, and the output of the eye tracker is automatically verified to be within range of this location on the display.…”
Section: Problem 2: When Eye Tracker Accuracy Deteriorates Below a Thmentioning
confidence: 99%
“…Many eye-tracking experiments entail tasks much more complex than looking at a set of crosshairs and then making a single saccade to a target (the task in Jonides, 1988, andAbrams et al, 1989). Eye trackers are becoming more widely used to monitor and evaluate eye movement patterns in realistic task settings, such as searching through a number of Web sites looking for information Pirolli, Card, & Van Der Wege, 2001).…”
Section: Problem 2: When Eye Tracker Accuracy Deteriorates Below a Thmentioning
confidence: 99%
“…It could also translate to more tightly clustered landing positions, meaning an effect on the spread or variance of landing position defined with respect to the centroid. We should note here that the speed and accuracy of eye movements are not independent and a speed/accuracy tradeoff is known to exist (e.g., [36]). Summary statistics for our data showed that the distance between the centroid of the target shape and the actual landing point of the saccade was negatively correlated to saccade latency, meaning that faster saccades indeed tended to be less accurate.…”
Section: Resultsmentioning
confidence: 99%
“…Note, however, that the numbers of corrective saccades did not differ between Word Positions 1, 3, and 5 in Experiment 3. Another possibility is that regressions for words located at the beginning of the sentence are less precise than for words located at the end because long saccades are less accurate than short saccades (see, e.g., Abrams, Meyer, & Kornblum, 1989). Clearly, more work needs to be done in order to understand how regressions are affected by word position and saccade programming.…”
Section: Discussionmentioning
confidence: 99%